Yusuf Al-Qaraḍāwī’s Theory of Zakat and Taxes and Its Relevance to Zakat and Taxation Law in Indonesia - Abdul Aziz, Jamal; Hamdan, Muhammad Sirajuddin Qahtan; Dahlan, Ahmad; Aprianto, Naerul Edwin Kiky (Journal of Ecohumanism, 2024)
This article aims to discuss Yūsuf al-Qaraḍāwī, one of the contemporary scholars whose thinking is considered moderate but progressive, especially regarding social reality. However, in this paper the focus of the study is on his views on zakat.Using descriptive qualitative methods based on reference data written by Yūsuf al-Qaraḍāwī, the following views were found; (1) ambiguity in placing zakat as ’ibāda (ritual worship) or ’āda/mu’āmala (general transaction); (2) zakat is separated from its historical and socio-political context; and (3) zakat must be different from tax.In this article, it is found that Yūsuf al-Qaraḍāwī’s view of zakat is dominated by theological interpretation, namely zakat as ’ibāda, so it is less dynamic when aligned with the taxation context. The sociological interpretation of zakat as the origin of taxation among Muslims tends to be ignored. His enthusiasm for differentiating zakat and taxes makes him less consistent in drawing out the common thread between zakat and taxes. However, there is something unique, Yūsuf al-Qaraḍāwī’s thoughts regarding zakat have become a reference for many zakat and endowment institutions in Indonesia.